1963
DOI: 10.1149/1.2425919
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Zirconium and Zirconium Alloys in Liquid Sodium

Abstract: The oxidation of zirconium and several zirconium alloys was investigated in the temperature range 400~176 in a static liquid sodium system with oxygen concentration approximately 10 ppm. A transition from a parabolic to a linear rate of oxidation was observed in the temperature region 400~176 for all of the zirconium alloys except Zircaloy-2. Above 500~ the transition was not observed, and a protective film continued to form. Using the parabolic rate equation to describe the kinetics of oxidation, activation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…ρ ment ΔG/S) does not depend on the oxygen concentration in the sodium (from the minimal concentration up to several hundreds ppm) [12,13]. At this concentration, the weight increment is also independent of the sodium velocity.…”
Section: Numerical Modeling Of Impurity Mass Transfer In Cold Traps Imentioning
confidence: 99%
“…ρ ment ΔG/S) does not depend on the oxygen concentration in the sodium (from the minimal concentration up to several hundreds ppm) [12,13]. At this concentration, the weight increment is also independent of the sodium velocity.…”
Section: Numerical Modeling Of Impurity Mass Transfer In Cold Traps Imentioning
confidence: 99%
“…Oxidation in liquid sodium.--It has been observed that zirconium oxidation in liquid sodium follows an approximate parabolic law and has an activation energy (10) of about 52 kcal/mole. What is the mechanism of oxidation in sodium and why is the rate constant about a factor of 100 larger (at 600~ for oxidation in oxygen than for oxidation in liquid sodium?…”
mentioning
confidence: 99%